Chapter Il fenomeno migratorio secondo i dati statistici - BLANGIARDO, GIAN CARLO (Studi e saggi, 2021)
A thorough understanding of the reality of migration is the best way to manage it and seize its value. For it, statistical data, can help do just that: they show that the foreign presence in Italy has not undergone major variations in recent years. A major part has been played by recent Italian citizenship acquisitions; and this takes place, paradoxically, while there is a much lamented lack of legislation and changes are invoked all round. Future perspectives seem to confirm, at least in the short term, a certain stability, generated by a weak attractiveness for "traditional" immigration and a significant maturation of older immigration components, accompanied by changes in status.